Olga Spence : many changes - Memorial University of Newfoundland. Extension Service (Producer)
Mrs. Olga Spence, a resident of Port au Choix for 53 years, talks about the many changes, both social and economic, that have taken place in the community. Ms. Spence worked as a telegraph operator for many years. Features Newfoundland traditional musician Rufus Guinchard on the fiddle at the beginning and end.